2018
DOI: 10.5144/0256-4947.2018.140
|View full text |Cite
|
Sign up to set email alerts
|

Turnover among Filipino nurses in Ministry of Health hospitals in Saudi Arabia: causes and recommendations for improvement

Abstract: BACKGROUNDNurse turnover is a critical challenge for healthcare organizations as it results in a decreasing nurse/patient ratio and increasing costs.AIMIdentify factors influencing the termination of Filipino nurses in Ministry of Health (MOH) hospitals and record nurse recommendations to improve retention.DESIGNCross-sectional.METHODSData was gathered from a convenience sample of Filipino nurses with previous experience in MOH hospitals in Saudi Arabia who attended recruitment interviews at the Saudi employme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 8 publications
2
22
2
Order By: Relevance
“…17,18 Many studies have identified the intention to quit nursing as a predictor of the ultimate decision. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The Nurses' Early Exit Study (NEXT), 20 found that ultimately, the decision to leave nursing is mostly taken within 6 months of actually doing so. It also been reported by Hasselhorn et al 20 that about 80% of nurses who left the profession began seriously considering the move within the previous year.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…17,18 Many studies have identified the intention to quit nursing as a predictor of the ultimate decision. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The Nurses' Early Exit Study (NEXT), 20 found that ultimately, the decision to leave nursing is mostly taken within 6 months of actually doing so. It also been reported by Hasselhorn et al 20 that about 80% of nurses who left the profession began seriously considering the move within the previous year.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nurses are a very diverse group of professionals, culture and alternative employment opportunities can have an impact on their intention to leave , the mindset that strengthened the idea, was "intention to leave" has often been probed, particularly using quantitative methods to determine associations with many variables that can influence nursing resolution to leave. 8,7,21 Occupational factors related to the "intention to leave" change the profession include hospital work environment, poor support from supervisors, lack of importance of the work, conflicting roles, and lack thereof in development opportunities. [14][15][16][17][18][19][20][21][22] Nurses' "intention to leave" in the professional capacity has been ascribed to psychosocial job strain ascertained by "demandcontrol-support" (DCS) 23 and "effort-reward imbalance" (ERI) 24 models.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to reach the recommended ratio of one nurse for every 200 Saudi citizens, KSA must recruit 185,722 expatriate nurses [2]. The recruitment of expatriate nurses throws up several challenges, including a competitive market, high turnover, financial costs, healthcare instability, and concerns regarding patient safety [3]. Therefore, establishing and enhancing domestic nursing education programs to meet the needs of the nursing workforce will be a key strategic requirement for the Saudi government.…”
Section: Introductionmentioning
confidence: 99%